2003
DOI: 10.1590/s0100-879x2003000600002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cellulose has no effect on the regeneration of hemoglobin in growing rats with iron deficiency anemia

Abstract: The objective of the present study was to determine the effect of cellulose on intestinal iron absorption in rats during recovery from iron deficiency anemia. Twenty-one-day-old male Wistar-EPM rats were fed an iron-free ration for two weeks to induce anemia. At 5 weeks of age, the rats were divided into two groups (both groups receiving 35 mg of elemental iron per kg diet): cellulose group (N = 12), receiving a diet containing 100 g of cellulose/kg and control (N = 12), receiving a diet containing no cellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
3
12
0
8
Order By: Relevance
“…Indeed, the same research team observed, in an excellent previous experiment, significantly greater ingestion of the diet containing cellulose than of the diet without DF. 10 In addition, in that experiment 10 exactly double the quantity of DF (100 g of cellulose per kg of diet), than in the experiment by Freitas et al, 8 was offered, generating a much higher fecal weight (10.7 vs. 5.2 g). According to Catani et al, 10 50 g of cellulose corresponds to 12.5 g of fiber per 1,000 kcal, which would be the recommended intake for children.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed, the same research team observed, in an excellent previous experiment, significantly greater ingestion of the diet containing cellulose than of the diet without DF. 10 In addition, in that experiment 10 exactly double the quantity of DF (100 g of cellulose per kg of diet), than in the experiment by Freitas et al, 8 was offered, generating a much higher fecal weight (10.7 vs. 5.2 g). According to Catani et al, 10 50 g of cellulose corresponds to 12.5 g of fiber per 1,000 kcal, which would be the recommended intake for children.…”
mentioning
confidence: 78%
“…10 In addition, in that experiment 10 exactly double the quantity of DF (100 g of cellulose per kg of diet), than in the experiment by Freitas et al, 8 was offered, generating a much higher fecal weight (10.7 vs. 5.2 g). According to Catani et al, 10 50 g of cellulose corresponds to 12.5 g of fiber per 1,000 kcal, which would be the recommended intake for children. However, taking into account the fecal characteristics of rats, it could be asked whether the higher DF proportion would be desirable.…”
mentioning
confidence: 78%
“…Se considera que la fibra impide la absorción de hierro a nivel intestinal (25) . Sin embargo, Feltrin señala que la fibra soluble de pectina no impide la absorción intestinal de hierro (26) .…”
Section: Discussionunclassified
“…Calculations were performed using Jandel Sigma Stat software. Sample size was calculated based on the results of a previous study performed at our laboratory, 13 in which it was observed that rats receiving rations with cellulose exhibited mean±standard deviation for humid fecal weight over three days of 10.7±3.5 g, while the group that received rations without fiber eliminated 1.9±1.2 g of feces during the same period.…”
Section: Methodsmentioning
confidence: 99%